2018
DOI: 10.1021/acs.nanolett.8b03201
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chain Atomic Crystals as Extracellular Matrix-Mimicking Material with Exceptional Biocompatibility and Bioactivity

Abstract: In this study, Mo 3 Se 3 − single-chain atomic crystals (SCACs) with atomically small chain diameters of ∼0.6 nm, large surface areas, and mechanical flexibility were synthesized and investigated as an extracellular matrix (ECM)mimicking scaffold material for tissue engineering applications. The proliferation of L-929 and MC3T3-E1 cell lines increased up to 268.4 ± 24.4% and 396.2 ± 8.1%, respectively, after 48 h of culturing with Mo 3 Se 3 − SCACs. More importantly, this extremely high proliferation was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 79 publications
(103 reference statements)
0
36
0
Order By: Relevance
“…Inorganic nanomaterials are promising candidates for fabrication of substrates with different dimensions. A recent study with a one-dimensional (1D) inorganic nanomaterial (molybdenum selenide, Mo 3 Se 3 − ) affirmed the enhanced cellular response to physical properties of materials, such as dimension comparable to ECM molecules, mechanical flexibility, and topography [34]. The authors reported high cell proliferation on 1D Mo 3 Se 3 − single chain atomic crystals (SCACs) (Figure 1).…”
Section: Engineered Materialsmentioning
confidence: 90%
See 2 more Smart Citations
“…Inorganic nanomaterials are promising candidates for fabrication of substrates with different dimensions. A recent study with a one-dimensional (1D) inorganic nanomaterial (molybdenum selenide, Mo 3 Se 3 − ) affirmed the enhanced cellular response to physical properties of materials, such as dimension comparable to ECM molecules, mechanical flexibility, and topography [34]. The authors reported high cell proliferation on 1D Mo 3 Se 3 − single chain atomic crystals (SCACs) (Figure 1).…”
Section: Engineered Materialsmentioning
confidence: 90%
“…The authors reported significant increases of proliferation of L-929 fibroblast and MC3T3-E1 osteoblast cell lines up to 268.4 ± 24.4% and 396.2 ± 8.1%, respectively, at 48 h post culturing with Mo 3 Se 3 − SCACs (Figure 1). 1D Mo 3 Se 3 − SCAC nanowire with negative surface charge, mechanical flexibility, large surface area, and small diameter (approximately 0.6 nm) mimicked ECM and improved the cellular response [34]. Furthermore, others prepared gold (Au) nanomaterials of different sizes and shapes (sphere, star, and nanorod) and demonstrated the effects of the materials on osteogenic differentiation of human mesenchymal stem cells (hMSC) and resulting alkaline phosphatase (ALP) activity and calcium deposition [35].…”
Section: Engineered Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CNTs treated with surfactants generally exhibit serious issues regarding stability; this is because, most surfactants detach from the CNT surfaces below their critical micelle concentrations owing to the dynamic dispersion phenomenon . Accordingly, passivation with polymers is generally preferred; this is because in addition to forming stable complexes with CNTs via hydrophobic interactions and preserving the intrinsic properties of CNTs, polymers facilitate the introduction of certain FGs on the surface of CNTs . However, considerable effort is required for the chemical modification of these polymers to obtain the desired FGs on the CNT surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…However, the dangling bonds on the edges in 2D materials still act as scattering centers 3 and recombination centers 4 when scaled down to less than a few tens of nanometers. In recent years, interest in 2D vdW materials has expanded to include one‐dimensional (1D) vdW structures comprising vdW‐bonded molecular chains 5–21 . There are two types of 1D vdW structures: a true 1D structure with a pure vdW interchain bond and a quasi‐1D structure with additional non‐vdW bonds among molecular chains.…”
Section: Introductionmentioning
confidence: 99%